Two new sponge inhabiting leucothoid amphipod species from the Western Atlantic - Cummings, Victoria M.; White, Kristine N.; Thomas, James Darwin (Zootaxa, 2023)
Two new leucothoid amphipod species are described from the Western Atlantic Ocean. Leucothoe mucifibrosa sp. nov., collected from Belize, may represent a member of the “Paraleucothoe” group with a specific sponge host preference. Leucothoe darthvaderi sp. nov., collected from South Florida, is part of the Leucothoe spinicarpa species complex and has demonstrated a shift in host preference over time, possibly associated with environmental perturbances.